Human Development Index: Comparative Status of Key Countries and the Context of Nepal - Ghimire, Laxmi (Prashasan: The Nepalese Journal of Public Administration, 2025)
Human development refers to the expansion of opportunities and freedoms for individuals. It encompasses the economic, social, and political transformation of people. It is associated with well-being and quality of life, ensuring equality and justice for all. The Human Development Index (HDI) varies among countries, with rankings ranging from 1 (highest) to 192 (lowest). HDI is generally measured using three key indicators: per capita income, life expectancy, and education. This article focuses on the concept, dimensions, components, and significance of human development. It presents a comparative analysis of the HDI of countries with very high human development. Additionally, it discusses the threshold criteria for graduating into a developing country and evaluates Nepal’s performance. The article further explores HDI components in relation to the Sustainable Development Goals, the challenges Nepal faces, and possible forward-looking solutions to improve its human development status. Based on the latest studies and reports, this article highlights Nepal’s position in the global Human Development Index.